2021
DOI: 10.1111/ejn.15252
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects SH‐SY5Y cells against MPP+‐induced declining of mitochondrial membrane potential and cell cycle deficits

Abstract: Dexmedetomidine (Dex), an adrenergic α2 receptor agonist, is commonly used in deep-brain stimulation surgery for Parkinson's disease (PD). However, there is evidence that the use of anaesthetics may accelerate the progression of neurodegenerative diseases. The effect of Dex on PD remains unclear. Here, we cultured the all-trans-retinoicacid (ATRA) differentiated SH-SY5Y cells in vitro and then treated with MPP + (1.5mM) with or without Dex (10nM) or Dex combined with Atipamezole (Ati,100nM, adrenergic α2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…3), causing a high green/red ratio signal compared to the untreated control condition. This result is in line with several other studies that demonstrated the ability of MPP+ to accumulate inside mitochondria, followed by depolarization of the MMP [37][38][39]. This includes a recent study by Mapa and others [40], where the authors utilized experimental conditions that overlapped with the present work, namely a similar dosage of MPP+ (500μM), but with the cell line (undifferentiated MN9D cells) that differed from that used here.…”
Section: Potentialsupporting
confidence: 91%
“…3), causing a high green/red ratio signal compared to the untreated control condition. This result is in line with several other studies that demonstrated the ability of MPP+ to accumulate inside mitochondria, followed by depolarization of the MMP [37][38][39]. This includes a recent study by Mapa and others [40], where the authors utilized experimental conditions that overlapped with the present work, namely a similar dosage of MPP+ (500μM), but with the cell line (undifferentiated MN9D cells) that differed from that used here.…”
Section: Potentialsupporting
confidence: 91%
“…Finally, FACS experiments confirmed that mitochondrial dysfunction and apoptosis were increased in 6-OHDA-and MPP+-treated SH-SY5Y cells (Fig. 1E, F), as reported in previous studies (Wang et al 2014;Chen et al 2021;Ganapathy et al 2016). These results indicate that neurodegeneration was induced in 6-OHDA-and MPP+-treated SH-SY5Y cells that simulated PD.…”
Section: Development Of In Vitro Pd Model Of Sh-sy5y Cells Treated Wi...supporting
confidence: 90%
“…Existing studies have shown that the increase of ROS and the decrease of ATP caused by mitochondrial dysfunction promote oxidative stress response, aging and neurodegenerative changes, which promote the occurrence and development of PD [ 54 , 55 ]. MPP + inhibits the function of respiratory complex I, interferes with the mitochondrial electron transport chain, and eventually leads to the decrease of mitochondrial membrane potential, the increase of ROS, and mitochondrial damage [ 55 , 56 ]. We observed that PPDs treatment restored mitochondrial membrane potential and reduced ROS accumulation, suggesting that PPDs could rescue mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%